MAXIMS OF POLITENESS ON ALICE IN WONDERLAND MOVIE (PRAGMATIC ANALYSIS) - Widyaningsih, Maulina; Hastuti, Erni (Journal of Language and Literature, 2018)
Politeness is ethics in socializing by using a good choice of words, and pay attention to where, when, to whom, and for what purpose we are talking. Politeness is a type of behavior allowed speaker to engage in social interaction in atmosphere of relative harmony. Thus, Leech specifies the maxim more carefully and comprehensively which constraint influencing speaker’s communicative behavior. The aims of this research are to identify and to analyze maxim of politeness in Alice in Wonderland movie. Data were analyzed using qualitative descriptive analysis methods with steps to reduce or choose the main subject then analyze and categorize according to maxim of politeness in movie conversation. The results showed that Alice in Wonderland movie consist of Maxim which proposed by Leech such as generosity, tact, approbation, modesty, agreement, and sympathy.